(untitled) (Global Journal of Human-Social Science, 2025)
This paper is descriptive in nature and examines various aspects of the Energy Sector as related to LNG. India’s energy sector must critically balance rising energy demands, environmental concerns, economics, and energy security. With the government’s goal to increase the share of natural gas in the energy mix from 6% to 15% by 2030, Liquefied Natural Gas (LNG) has emerged as a critical energy component. LNG is a method for transporting natural gas over long distances when pipelines are not feasible. The article examines LNG’s expanding role in India’s energy portfolio, focusing on several key aspects, including economic advantages, energy security, and generating local employment through the development of LNG infrastructure. Environmentally, LNG significantly reduces air pollutants and CO₂ emissions. Challenges to LNG adoption are also considered, including infrastructure deficits, regional accessibility issues, price volatility, and competition from renewable energy sources. The article concludes by discussing the future of LNG in India’s energy mix, recommending further investment in infrastructure, stable LNG pricing, and policy measures to support LNG’s role as a transition fuel. It also recommends steps for the Government and the LNG industry to maximize the use of this form of energy. By addressing these challenges, LNG can play a strategic role in enhancing India’s energy security, environmental sustainability, and economic resilience.